Elemen-elemen Perubahan dalam Kurikulum 2013 - Lubis, Chairul Azmi (ALSYS, 2022)
The 2013 curriculum is the development of the Competency-Based Curriculum which was pioneered in 2004 and the 2006 KTSP. Teachers must have adequate and mature readiness, starting from readiness in terms of qualifications, competencies and also being ready in terms of common understanding and mindset towards the curriculum. the new. The learning process that encourages students to be active is only possible if the teacher's mindset has changed, has been running in accordance with the direction and changes of the 2013 Curriculum. Failure to change the teacher's mindset will be a source of failure to implement the 2013 Curriculum. The problem is that changes in the teacher's mindset cannot be done in a short time. According to the Ministry of Education and Culture of the Republic of Indonesia, the focus of developing the 2013 curriculum is to reduce the number of subjects, reduce subject matter and increase lesson hours. Referring to Government Regulation No. 32 of 2013 concerning National Education Standards, there are four changes to this new curriculum, namely: First, Changes to Graduation Standards/SKL (Permendikbud no. 54 of 2013). Second, changes to content standards (Permendikbud no. 64 of 2013). Third, changes to process standards (Permendikbud no. 65 of 2013) and Fourth. Changes in the assessment aspect (Permendikbud no. 66 of 2013). While the other four standards did not change.